A judicialização reversa como estratégia de dominação nas políticas públicas sobre terras quilombolas - Bottega, Clarissa (Universidade do Vale do Rio dos Sinos, 2022)
This work investigates how to break the paradigms related to common sense that involves the comprehension of the judicialization institute of public politicals and presents a new horizon for the institute perception, despite having been created in search of the effectiveness of democracy, it can be distorted and used with the objective of de-democratization. The proposal followed the path of political science with a detailed analysis of the speeches present in the ADI nº 3.239/2004, which objectify the Federal Decree nº 4.887/2003 abrogation. The act was proposed by a political party with a capitalist and liberal base against the decree that objectify to regularize the land title of quilombola lands. One of the demand argumentative points was the conceptual dispute about the concept of quilombo, once the impugned decree presents quilombola self-allocation as one of the requirements for access the land rights. The use of the concept of historic quilombo or contemporary quilombo is a crucial point for restriction or expansion of subjects of law provided at art. 68 of the ADCT, which guarantees the land right for quilombola communities, and the impugned decree is the effective way to access this fundamental right. Therefore, when the ruling class impress the historical quilombo concept definition, it is to restrict the subjects of rights and keep the land under the ownership of the large landowners. For quilombola communities, expanding the understanding of the concept of quilombo (contemporary) is more than the recognition and guarantee of rights, reflecting a necessity for citizenship today and not in the past. Class struggles, domination and the perpetuation of inequalities permeate the discourses and constant manifestations of the analyzed process and reflect the use by the ruling class of legal instruments daily understood as democracy defenders in favor of their hidden interests.
Keywords: Judicialização; Políticas públicas; Quilombos; Direito à terra; Cidadania; Judicialization; Public politicals; Land rights; Citizenship; ACCNPQ::Ciências Humanas::Sociologia